2011
DOI: 10.1089/vbz.2010.0265
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of a Point-of-Care Immunochromatographic Test SNAP 4Dx with Molecular Detection Tests for Vector-Borne Canine Pathogens in Hong Kong

Abstract: There are no comprehensive studies on the performance of commonly used point-of-care diagnostic enzyme immunoassay for common arthropod-borne canine pathogens. A comparative evaluation of an immunochromatographic test for these infections with a comprehensive polymerase chain reaction (PCR) test panel was performed on 100 pet dogs and 100 stray dogs without obvious clinical symptoms. Of the 162 positive test results from both immunochromatographic test and PCR, there was 85.2% concordance. The 24 discordant re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
24
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 46 publications
4
24
0
1
Order By: Relevance
“…Our previous study showed that D. immitis can be found in 10% of stray dogs in Hong Kong (34). All infected dogs also had detectable Wolbachia DNA in the blood.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Our previous study showed that D. immitis can be found in 10% of stray dogs in Hong Kong (34). All infected dogs also had detectable Wolbachia DNA in the blood.…”
Section: Discussionmentioning
confidence: 93%
“…Blood samples collected from the asymptomatic stray dogs were tested for antigen of D. immitis using SNAP 4Dx (IDEXX Laboratories, Westbrook, ME) as we previously described (34).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These are not only more convenient and generally cheaper than traditional serological techniques (e.g., immunofluorescent antibody testing), they have the important advantage in the clinical setting of empowering the veterinarian to provide immediate treatment for the pet and advice to the owner. An additional benefit of these tests, often with in-kind support provided by the manufacturers, has been an increase in the number of cross-sectional serosurveys of CVBDs around the world, which have greatly furthered our understanding of their epidemiology and geographical distribution [41,42]. Nevertheless, it should be remembered that such tests also have limitations in terms of sensitivity (e.g., acute infections prior to antibody response) and specificity (e.g., cross-reactions between organisms), and some clinically significant diseases (e.g., acute babesiosis) are still probably best diagnosed by microscopy [43,44].…”
Section: Paradigm 2: Maintain the (Clinical) Vigilancementioning
confidence: 99%
“…abesiosis is the commonest vectorborne canine infection in Hong Kong, with 48% and 33% of the stray and pet dogs being infected, respectively (14). Human babesiosis is usually caused by Babesia microti, B. divergens, and some newly described strains such as the WA1, EU1, -2, and -3, CA1, -2, -3, and -4, and KO1 types (9).…”
mentioning
confidence: 99%